Strengthening the Buddy Program is an Effort to Prevent Acts of Violence in the School Environment - Nahuda; Mugiyono; Ts Hj Mohd Hilmi bin Bakar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Violence in schools, whether physical, verbal, psychological, or social, remains a serious problem that threatens a safe and character-building educational climate. Bullying, intimidation, and social exclusion not only impact students' academic achievement but also impact their mental health, self-confidence, and personality development. One approach considered effective and contextual in preventing violence in schools is the implementation of the Buddy Program, a peer mentoring program that systematically connects students in supportive, egalitarian, and socially conscious relationships. The purpose of this study was to analyze the strengthening of the Buddy Program as a preventive strategy to suppress and prevent acts of violence in schools. This research used a qualitative approach with a case study design, focusing on educational units that have implemented the Buddy Program as part of their character-building and violence prevention policies. The results showed that strengthening the Buddy Program was able to build more positive social relationships among students, increase empathy, and strengthen social support networks within the school environment. The presence of buddies provides a safe space for students vulnerable to violence to express their feelings, share problems, and receive emotional support